Corporate Governance Couture: Tailoring Financial Performance in the Indonesian Textile and Garment Sector - Awwaliyah, Intan Nurul; Wilantari, Regina Niken; Susanto, Arnis Budi; Prajitiasari, Ema Desia; Sukandar, Gabriella (KnE Social Sciences, 2024)
This research aims to determine the impact of institutional ownership, managerial ownership, independent commissioners, audit committees, and firm size on the financial performance of textile and garment industry sub-sector companies within the period of 2016 to 2021. By adopting an explanatory research approach, the study focuses on a population of textile and garment sub-sector companies listed on the Indonesian Stock Exchange, a total of 21 companies, selected through purposive sampling. Multiple linear regression analysis was employed as the analytical method. The findings indicate that institutional and managerial ownership does not significantly impact the financial performance of the examined companies. However, independent commissioners, active audit committees, and firm size significantly influence financial performance, supporting the critical role of these corporate governance mechanisms and firm characteristics in shaping financial outcomes within the Indonesian textile and garment sector. The study contributes to understanding the complex relationship between corporate governance mechanisms, firm characteristics, and financial performance. Future research should consider expanding the sample size and exploring other variables influencing financial performance in the textile and garment industry. Furthermore, investigating the mediating or moderating effects of other contextual factors or industry-specific characteristics could provide deeper insights into the observed relationships. Keywords: audit committee, firm size, good corporate governance, independent commissioner, institutional ownership, managerial ownership, ROE